Laser imaging for rapid Microbial Source Tracking. (12th January 2011) - Chen, Bin; Gong, Hao; Zhang, Xu; Patankar, Prithviraj P.; Sadowsky, Michael; Tseng, Charles
DNA fingerprinting, PCR and other genomic technologies have recently been used to determine sources of fecal bacteria in waterways. Here, we report on the development of a simple and automated optical method for potential use in Microbial Source Tracking (MST) of E. coli. The method employs laser imaging of bacterial colonies and high-resolution optical scattering image analysis for information extraction and classification. Cross validation is used to statistically evaluate the robustness of the classifiers. The entire image analysis procedure can be fully automated, making this a potentially useful tool for future MST studies.